Kolaborasi Pengurus dan Gen Z dalam Tata Kelola Masjid Secara Modern yang Efektif - Rina Gusmawati; Noor Fadlli Marh (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This paper is motivated by the condition of the Nurul Firdaus Mosque, which has long been neglected and has minimal religious activities other than Maghrib and Isha prayers. This phenomenon reflects the decline in the mosque's role as a center of worship and social and religious activities in the community. Mosques, which should be places for fostering the community, are instead only used to a limited extent, often even locked outside of Maghrib and Isha prayer times. This study aims to explore in depth the factors causing low congregation participation and find solutions in the form of innovative collaboration between mosque administrators and the younger generation, especially Generation Z, in managing the mosque in a modern and inclusive manner. The method used is a descriptive qualitative approach with data collection techniques through in-depth interviews and documentation. Informants in this study consisted of religious leaders, community leaders, mosque administrators, mosque youth, and the general public living around the research location. The research focuses on examining social dynamics, communication patterns, and forms of participation between groups involved in mosque management. Anthony Giddens' structuration theory is used as an analytical tool to understand the relationship between structures (rules, norms, and practices of mosque management) and agents (mosque administrators and youth) in shaping social change towards more open, adaptive, and responsive mosque management to the needs of the times. The results of the study indicate that the alienation of the congregation towards the mosque is influenced by the lack of innovation in religious activities, the absence of an accommodating approach to the younger generation, and weak communication and coordination within the mosque management body itself.